Evaluation of organizational excellence based on Peters and Waterman\'s model in Engineering Company of Isfahan Ghaem Sepahan - Batul Forouzan; Ali Attafra (مدیریت تولید و عملیات, 2013)
The objective of this paper is to study organizational excellence based on Peters and Waterman model in Engineering Company of Isfahan Ghaem Sepahan . Eight variables have been evaluated in this model including bias for action close to the customer autonomy and entrepreneurship productivity through people hands-on, value-driven stick to the knitting simple form, lean staff and simultaneous loose-tight properties . This research is typically descriptive and practical. Statistical population includes employees of Engineering Company of Isfahan Ghaem Sepahan . The sample size is 89 and is selected through random sampling method. Data has been collected by means of researcher self-made questionnaire with 45 questions and Likert’s five point scale. One variable t-test, T2 Hotelling and multi-variable variance analysis have been used for statistical analysis. Results reveal that the observed t is higher than the average level regarding Peters and Waterman organizational excellence variables. As a result, this company is an excellent organization based on the model. Finally, based on the studied model, a systematic approach has been developed.